2022
DOI: 10.21203/rs.3.rs-1499064/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of Professional Midwives and Mentoring on the Quality and Availability of Maternity Care in Rural Government Hospitals in Bangladesh

Abstract: Background This study examined whether the introduction of professional midwives with and without facility mentorship improved care quality and availability in sub-district hospitals in Bangladesh. It also analysed the experiences of non-midwife maternity care providers and managers. Methods Using mixed-methods, differences between hospitals without midwives, with midwives, and with mentorship were explored. Quantitative analysis comprised observations of facility readiness and clinical care to assess imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“… 1 Traveling significant distances for routine PNC may cause substantial financial constraints or transportation difficulties for rural women. 3 Studies have found that restricted access to public transportation and long transit times played a significant role in the amount of PNC received. 4 Furthermore, difficulty recruiting and retaining rural obstetricians was a major factor in the inability to provide PNC and intrapartum care.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Traveling significant distances for routine PNC may cause substantial financial constraints or transportation difficulties for rural women. 3 Studies have found that restricted access to public transportation and long transit times played a significant role in the amount of PNC received. 4 Furthermore, difficulty recruiting and retaining rural obstetricians was a major factor in the inability to provide PNC and intrapartum care.…”
Section: Introductionmentioning
confidence: 99%